Visual Sensory Processing is Altered in Myoclonus Dystonia. Issue 1 (30th September 2019) - Tarrano, Clément; Wattiez, Nicolas; Delorme, Cécile; McGovern, Eavan M.; Brochard, Vanessa; Thobois, Stéphane; Tranchant, Christine; Grabli, David; Degos, Bertrand; Corvol, Jean‐Christophe; Pedespan, Jean‐Michel; Krystkoviak, Pierre; et al.
ABSTRACT: Background: Abnormal sensory processing, including temporal discrimination threshold, has been described in various dystonic syndromes. Objective: To investigate visual sensory processing in DYT‐ SGCE and identify its structural correlates. Methods: DYT‐ SGCE patients without DBS (DYT‐ SGCE ‐non‐DBS) and with DBS (DYT‐ SGCE ‐DBS) were compared to healthy volunteers in three tasks: a temporal discrimination threshold, a movement orientation discrimination, and movement speed discrimination. Response times attributed to accumulation of sensory visual information were computationally modelized, with μ parameter indicating sensory mean growth rate. We also identified the structural correlates of behavioral performance for temporal discrimination threshold. Results: Twenty‐four DYT‐ SGCE ‐non‐DBS, 13 DYT‐ SGCE ‐DBS, and 25 healthy volunteers were included in the study. In DYT‐ SGCE‐ DBS, the discrimination threshold was higher in the temporal discrimination threshold ( P  = 0.024), with no difference among the groups in other tasks. The sensory mean growth rate (μ) was lower in DYT‐ SGCE in all three tasks ( P  < 0.01), reflecting a slower rate of sensory accumulation for the visual information in these patients independent of DBS. Structural imaging analysis showed a thicker left primary visual cortex ( P  = 0.001) in DYT‐ SGCE ‐non‐DBS compared to healthy volunteers, which also correlated with lower μ in temporal discrimination threshold ( P  = 0.029). In DYT‐ SGCE ‐non‐DBS, myoclonus severity also correlated with a lower μ in the temporal discrimination threshold task ( P  = 0.048) and with thicker V1 on the left ( P  = 0.022). Conclusion: In DYT‐ SGCE, we showed an alteration of the visual sensory processing in the temporal discrimination threshold that correlated with myoclonus severity and structural changes in the primary visual cortex. © 2019 International Parkinson and Movement Disorder Society